AKTIVITAS BELAJAR SISWA TERHADAP MEDIA VIDEO TUTORIAL TOPIK POTONGAN SAYURAN DI SMK R.A KARTINI BANDUNG - Tina Septiana, - (2018)
Media pembelajaranmampumenciptakaninteraksisecaralangsungantarasiswadengansumberbelajar, memungkinkansiswabelajaraktif, mandirisesuaidenganbakatdankemampuan visual, auditoridankinestetiknya. Media video tutorialmendorongkegiatanpembelajarandenganmelibatkanimajinasidanaktivitasbelajarsiswa di dalamkelas.Tujuandaripenelitianiniuntukmengetahuiaktivitasoral danmotoriksiswadalamkegiatanpembelajaransetelahditayangkanmedia video tutorial topikpotongansayuranpadamatapembelajaranBogaDasar di SMK R.A Kartini Bandung.Partisipanpenelitianyaitusiswakelas X keahlianJasaBoga.Metode yang digunakanpadapenelitianiniyaitudeskriptifdenganpendekatankuantitatif. Penelitimelakukanobservasidanwawancarasebagaiteknikpengambilan data.Hasilpenelitianmenunjukkanbahwaaktivitas oral siswaberadapadakategoriaktifdanaktivitasmotoriksiswaberadapadakategoriaktif.Diharapkanguru matapelajaranBogaDasardapatmemanfaatkan media pembelajarandenganlebihbaikgunameningkatkanaktivitasbelajarsiswa di dalamkelas.;---Media of learning has the potential to build a direct interaction between students and their learning sources, makes it possible for student to learn actively, independently, and appropriately according to their skills and visual, auditory, and kinetic abilities. The media of tutorial videos propels learning activities by involving imagination and students' actual learning activities in the classroom. The purpose of this study serves to reveal students' oral and motoric activities in a learning situation after being exposed to the tutorial videos with the topic of vegetable cuttings as the media of learning in the subject of BogaDasar(Basic Culinary Arts) at SMK R.A Kartini Bandung. The participants in this study involve Grade 10 students majoring in JasaBoga(Culinary Services). Descriptive analysis with quantitative approach is used as the methodology for this study. The researcher conducted observation and interviews as the technique of data collection. The result shows that students' oral and motoric activities are categorized as active. From this study, the teachers of Basic Culinary Arts are expected to utilize media of learning in a better way to improve students' learning activities in the classroom.;---